Hidrogeoquímica e qualidade das águas superficiais na Bacia do Alto Jacaré-Pepira (SP) - Batista, Ludmila Vianna [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Hydrochemical studies in catchments has been used with the main purpose to evaluate the water quality, as well as establishing the water/rock-soil interactions which are responsible for print ingthe main chemical characteristics to surface water. Inserted in UGRHI-13, the watershed of Alto Jacaré-Pepira/SP was selected due to its geological complexity and location in the recharge area of the Guarani Aquifer System (GAS), also because water resources are an important tourist attraction, especially for the city of Brotas (SP). 17 samples of surface water were collected along two sampling campaigns, the first between days 10 to 30 of July 2013, and the second between days 18 March to 1 April 2014, in order to determine the WQI (Water Quality Index), as well as to evaluate its chemical composition and establish the geochemical processes responsible for their composition. The WQI results were compared with CETESB monitoring points located along the Jacaré-Pepira River, and indicated that the water quality can be considered good, with WQI values ranging between 63 and 82 in the summer season, and 59- 75 in the winter season. The presence of HCO3 -, Ca2+ e Mg2+ ions as predominant is compatible with the weathered basalt and sandstone rocks, present in the Serra Geral and Botucatu/Pirambóia formations, constituents of the local geological framework. In common, all samples were classified as bicarbonate-calcic or magnesian. This study assessment of the samples allowed the observation of the small influence of human action on the chemical composition of the water, reflected in high levels of IQA, and the low concentrations of Cl- and NO3 -, and the dissolution of minerals from the geological substrate the main source of elements dissolved in surface water in the Upper Basin Jacaré-Pepira. The values found for the isotopic ratios (δ2H e δ18O) indicate meteoric origin to the waters of the sub-basin of the Jacaré-Pepira River, distinguishing ...

A hidroquímica vem sendo utilizada como ferramenta para avaliar se a qualidade das águas sofre alteração devido a ação antrópica, bem como estabelecer quais as interações existentes entre água/rocha-solo, e que fornecem as características finais das águas superficiais. Inserida na UGRHI-13, a sub-bacia do Alto Jacaré Pepira/SP foi selecionada em função de sua complexidade geológica e por representar uma importante área de recarga do Sistema Aquífero Guarani (SAG), na qual os recursos hídricos representam uma importante atração turística, especialmente para a cidade de Brotas (SP). Foram coletadas 17 amostras de águas superficiais em duas campanhas de amostragem, a primeira entre os dias 10 a 30 do mês de julho de 2013, e a segunda entre os dias 18 de março à 1° de abril de 2014, com o objetivo de se determinar o IQA (Ííndice de Qualidade de Águas), bem como avaliar sua composição química e estabelecer os processos geoquímicos responsáveis pela sua composição. Os resultados de IQA foram comparados com dois pontos monitoramento da CETESB no Rio Jacaré-Pepira, e indicaram que a qualidade da água pode ser considerada boa, com valores de IQA que variam de 63 a 82 na campanha de verão, e 59 a 75 na campanha de inverno. A presença de HCO3 -, Ca2+ e Mg2+ como íons predominantes é compatível com o intemperismo de rochas basálticas e areníticas, presentes nas formações Serra Geral e Botucatu/Pirambóia, constituintes do arcabouço geológico local. Em função dessa composição, as águas foram classificadas como bicarbonatada-cálcica ou magnesiana. A avaliação global das amostras possibilitou a constatação da pequena influência exercida pela ação antrópica na composição química das águas, refletida nos valores elevados de IQA, e pelas baixas concentrações de Cl- e NO3 -, sendo a dissolução de minerais do substrato geológico a principal fonte dos elementos dissolvidos nas águas...
Keywords: Water - Composition; Agua - Composição; Água - Qualidade; Quimica da agua; Isotopos; Jacare Pepira, Rio (SP)